Empowering Employees With Glamping As An Alternative Accommodation In The New Normal Era In Kembang Merta Village, Tabanan Regency, Bali Province - Ni Desak Made Santi Diwyarthi Diwyarthi; Ni Nyoman Sukerti; I Dewa Hendri Pramana; I Wayan Jata (UNUSA Press, 2022)
The pandemic situation and the strict health protocols implemented have resulted in tourist visit decline and hotel occupancy rates decline. The government and hotel management carry out various potential businesses for the accommodation service business. In the midst of intense industry competition, the accommodation service business seeks to develop the right marketing mix by finding and understanding tourists' desires, so as to encourage tourists' decisions to stay. Tourists have different preferences for the attributes of accommodation service businesses. One of the things that are trending for tourists is choosing attractive, safe and comfortable accommodation, returning to nature, avoiding large crowds during the Covid-19 pandemic. The alternative presented by accommodation service entrepreneurs is glamping. Glamping is a contemporary phenomenon as an alternative accommodation for tourists. This glamorous camping (glamping) concept presents an alternative in camping, but still provides a sense of security and comfort in enjoying the natural atmosphere (Monita, 2019, Ferdian, 2020). Candi Kuning Tourism Village has succeeded in showing the readiness of glamping management in accepting tourists with health protocols according to the government’s rule. The revival of Bali tourism is also marked by the stretching of the increase in glamping occupancy in Candi Kuning Tourism Village, Baturiti District, Tabanan Regency. This proves the success of glamping management in a new normal era tourism, based on Industry 4.0 and Society 5.0.